The use of chest ultrasonography in suspected cases of COVID-19 in the emergency department - Allegorico, Enrico (Future Sci OA, 2020)
AIM: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus-specific reverse transcriptase-polymerase chain reaction (RT-PCR) represents the diagnostic gold standard. We explored the value of chest ultrasonography to predict positivity to SARS-CoV-2 on RT-PCR in suspected COVID-19 cases. PATIENTS & METHODS: Consecutive patients with suspect COVID-19 were included if they had fever and/or history of cough and/or dyspnea. Lung ultrasound score (LUSS) was computed according to published methods. RESULTS: A total of 76 patients were included. A 3-variable model based on aspartate transaminase (AST) > upper limit of normal, LUSS >12 and body temperature >37.5°C yielded an overall accuracy of 91%. CONCLUSION: A simple LUSS-based model may represent a powerful tool for initial assessment in suspected cases of COVID-19.